Endplate denervation correlates with Nogo‐A muscle expression in amyotrophic lateral sclerosis patients. (16th February 2015) - Bruneteau, Gaëlle; Bauché, Stéphanie; Gonzalez de Aguilar, Jose Luis; Brochier, Guy; Mandjee, Nathalie; Tanguy, Marie‐Laure; Hussain, Ghulam; Behin, Anthony; Khiami, Frédéric; Sariali, Elhadi; Hell‐Remy, Caroline; Salachas, François; et al.
Abstract Objective Data from mouse models of amyotrophic lateral sclerosis (ALS) suggest early morphological changes in neuromuscular junctions (NMJs), with loss of nerve–muscle contact. Overexpression of the neurite outgrowth inhibitor Nogo‐A in muscle may play a role in this loss of endplate innervation. Methods We used confocal and electron microscopy to study the structure of the NMJs in muscle samples collected from nine ALS patients (five early‐stage patients and four long‐term survivors). We correlated the morphological results with clinical and electrophysiological data, and with Nogo‐A muscle expression level. Results Surface electromyography assessment of neuromuscular transmission was abnormal in 3/9 ALS patients. The postsynaptic apparatus was morphologically altered for almost all NMJs (n = 430) analyzed using confocal microscopy. 19.7% of the NMJs were completely denervated (fragmented synaptic gutters and absence of nerve terminal profile). The terminal axonal arborization was usually sparsely branched and 56.8% of innervated NMJs showed a typical reinnervation pattern. Terminal Schwann cell (TSC) morphology was altered with extensive cytoplasmic processes. A marked intrusion of TSCs in the synaptic cleft was seen in some cases, strikingly reducing the synaptic surface available for neuromuscular transmission. Finally, high‐level expression of Nogo‐A in muscle was significantly associated with higher extent of NMJ denervation and negative functional outcome. Interpretation Our results support the hypothesis that morphological alterations of NMJs are present from early‐stage disease and may significantly contribute to functional motor impairment in ALS patients. Muscle expression of Nogo‐A is associated with NMJ denervation and thus constitutes a therapeutic target to slow disease progression.